Investigation of the Efficiency of Motor based on Temperature for Agriculture Application - PAIYADH, MOHAMMAD FARHAN ADLI BIN PAIYADH; Ariffin, Ahmad Hamdan (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Drone is widely used in various industries in the world in line with the era of modernisation especially for medium farmers. This problem gives a challenge for small and medium farmers to adapt new technology in the aspects of drones due to expensive price of drones. The combination of high optimization of efficiency of motor with moderate price are required to decrease the price of drone. The selection of motor is one of the ways to reduce the price of drones. The efficiency of motor is one of the criteria to be considered before selecting the motor for drone. This project outlines a methodology for investigating the efficiency of the motor based on the temperature. This study focuses on how temperature could affect the efficiency and the thrust performance of the motor that could be used in agriculture industry. The experiment was conducted by using 5 kinds of motor to gain each of their RPM, throttle percentage, current load of motor, thrust force, power of motor, ambient temperature and temperature of motor. The lowest reading of RPM at the lowest temperature of motor is 670 rpm for M8 brushless dc motor, 889 rpm for M8 Pro brushless dc motor, 890 rpm for T-motor, 990 rpm for Agras T-10 motor and 1552 rpm for 10015/75kv motor. The highest efficiency of motor at lowest temperature is 19.23 g/W for M8 brushless dc motor. Results were organised by temperature (motor) vs RPM, temperature (motor) vs power, temperature (motor) vs thrust force, ambient temperature vs RPM, ambient temperature vs power and ambient temperature vs thrust force. Based on all condition in the graphs, the best motor is M8 Brushless direct-current motor because the lowest reading of RPM at the lowest temperature of motor was 670 rpm, lowest reading of power at the lowest temperature of motor was 13 watts and lowest reading of power at the lowest temperature of motor was 250 gf. The results showed that based on all these conditions, the efficiency of the motor is 19.23 g/W. If improvement is needed, a detailed study is needed.